Personality, pathogenic types in university students - Vicuña Peri, Luis A. (2001)
The last 30 years of psychological investigation they allow us to affirm that many physical illnesses don 't have as unique etiologic to exogenous factors; great part of them takes place for the weakening of the immunology system, consequence of concomitant sequels of the stress stale, as Chesney describes it (1980), Eysenck (1987-1988), Grossarth-Maticek (1988) among others. This investigation looks for to respond to the query They are significant differences in function to the sex and the professional election in a sample of university students first years old in the UNMSM, of the Abilities of Psychology and Education according to the six types of personality evaluated with the Inventory of Interpersonal Reactions of Eysenck and Grossarth-Maticek.